2004
DOI: 10.1088/0957-4484/16/1/009
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrochemical properties of nanosized NiO via thermal decomposition of nickel oxalate nanofibres

Abstract: Nickel oxide nanoparticles with an average diameter of about 9 nm were synthesized via thermal decomposition of NiC2O4 precursor at 450 °C. The nanoparticles were investigated using XRD, TEM, TGA, and UV–vis spectrophotometry. The optical absorption spectrum indicates that the NiO nanoparticles have a direct band gap of 3.56 eV. The electrochemical tests show that the ultrafine NiO nanoparticles, as a promising electrode material, can deliver a large reversible discharge capacity of about 610 mA h g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(80 citation statements)
references
References 15 publications
3
77
0
Order By: Relevance
“…18 Extensive studies have been reported over a last decade on particle size dependent magnetic properties [10][11][12] and finite size versus surface effects on magnetic properties, 19 effect of substitution, 20 and room temperature magnetic crossover [21][22][23][24] of NiO prepared by various techniques. A combined experimental and computation study carried out by Yi et al showed a remarkable size-dependent magnetism with large magnetization of 105 emu/g and ferromagnetic ordering temperature of 35 K, when the size of the NiO cluster is about 1 nm.…”
Section: Introductionmentioning
confidence: 99%
“…18 Extensive studies have been reported over a last decade on particle size dependent magnetic properties [10][11][12] and finite size versus surface effects on magnetic properties, 19 effect of substitution, 20 and room temperature magnetic crossover [21][22][23][24] of NiO prepared by various techniques. A combined experimental and computation study carried out by Yi et al showed a remarkable size-dependent magnetism with large magnetization of 105 emu/g and ferromagnetic ordering temperature of 35 K, when the size of the NiO cluster is about 1 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Stoichiometric NiO at R.T is an insulator with a resistivity of 10 13 Ω cm.The electrical conductivity of NiO can be manipulated by changing the concentration of Ni ion during doping [2]. Nickel oxide has demonstrated excellent properties such as catalytic [3] , magnetic ,electrochromic ,optical and electrochemical properties [4]. Znic is a first transition element in group 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The UV-Vis absorption peak was observed at 274 nm and the transmittance at 296 nm for the synthesized SrO NPs. The peak at 274 nm occurs due to the quantum size effect of monodispersed colloidal particles and the transmittance peak indicates the controlled size of particles and purity of the sample [28]. Athar reported the UV-Vis spectrum with broad spectrum at 265 nm and 290 nm which is due to the quantum size effect and surface morphology of the particles, respectively [11].…”
Section: Optical Propertiesmentioning
confidence: 96%